Hume and Wittgenstein: The risk of reasoning religion into superstition - Ellis David (Belgrade Philosophical Annual, 2024)
Hume argues that Christianity would be a superstitious delusion if it were based on the testimonial evidence that Christ performed miracles. Wittgenstein argues that those who base religious belief on evidence are 'ridiculous' and that evidence turns religion into 'superstition'. Despite appearing to undermine Christianity, I argue that Hume and Wittgenstein defend Christianity from being undermined when contextualised in their philosophical project. Their philosophical project aims to show what Christianity is like, and they show that it would be a superstitious delusion if it were based on evidential reasoning. Therefore, if we think Christianity is not a superstitious delusion then we should think it is based on something else. Hume calls this something else 'faith' but doesn't tell us much about it nor what miracles do for it. Wittgenstein, however, does, and his views not only map Hume's but offer insight into Christian life. Read in this way, both philosophers remind us that Christ came to save souls through faith, not minds through reason.